Antireflux Metal Stent With an Antimigration System for Distal Malignant Biliary Obstruction: A Feasibility Pilot Study. Issue 3 (June 2015) - Hamada, Tsuyoshi; Isayama, Hiroyuki; Nakai, Yousuke; Togawa, Osamu; Kogure, Hirofumi; Takahara, Naminatsu; Mohri, Dai; Sasaki, Takashi; Matsubara, Saburo; Yamamoto, Natsuyo; Hirano, Kenji; Tada, Minoru; et al.
Abstract : An antireflux metal stent (ARMS) for distal malignant biliary obstruction has been reported to be useful, but the effectiveness of a flared-end structure to prevent migration on ARMS remains unclear. To evaluate the feasibility of a newly designed ARMS with both ends flared, 8 patients with covered metal stent occlusion due to sludge or food impaction were enrolled. ARMS were placed successfully after endoscopic removal of the occluded stents in all patients, and no procedure-related complication was observed. The median time to recurrent biliary obstruction was 71 days. ARMS occlusion occurred in 3 (38%) patients (sludge in 2 patients and hemobilia in 1). ARMS migration occurred in 1 (13%) patient. As a late complication, cholecystitis occurred in 1 (13%) patient. In conclusion, our newly designed ARMS with an antimigration system was technically feasible and safe, and a further investigation is warranted to evaluate the effectiveness of the current antimigration system.